2010
DOI: 10.1128/aac.01607-09
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Efflux and Influx Modulate both Multidrug Resistance and Virulence of Klebsiella pneumoniae in a Caenorhabditis elegans Model

Abstract: Cross-resistance to cefoxitin (FOX), chloramphenicol (CMP), and quinolones (nalidixic acid [NAL]) related to a putative efflux system overexpression has recently been reported for Klebsiella pneumoniae. The potential impact of this multidrug resistance (MDR) on the virulence of K. pneumoniae was evaluated in the Caenorhabditis elegans model. For 2 of the 3 MDR clinical isolates studied, a significant increase in acrB transcription was found in comparison with their antibiotic-susceptible revertants. ATCC 13882… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 37 publications
(49 reference statements)
3
44
0
Order By: Relevance
“…We had previously shown in K. pneumoniae clinical isolates that cefoxitin, quinolone, and chloramphenicol cross-resistance was not always associated with an increase in the transcription level of the genes encoding AcrAB, the most frequently investigated efflux pump in Enterobacteriaceae (3). Interestingly, such a feature was also found in one of our 17 mutants, KPBj5 M1 …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We had previously shown in K. pneumoniae clinical isolates that cefoxitin, quinolone, and chloramphenicol cross-resistance was not always associated with an increase in the transcription level of the genes encoding AcrAB, the most frequently investigated efflux pump in Enterobacteriaceae (3). Interestingly, such a feature was also found in one of our 17 mutants, KPBj5 M1 …”
Section: Discussionmentioning
confidence: 56%
“…The collection studied comprised (i) 3 previously published K. pneumoniae clinical isolates shown to have cross-resistance to cefoxitin, quinolones, and chloramphenicol (KPBj Eϩ), with increased expression of the acrB gene for 2 of them (KPBj1 Eϩ and KPBj3 Eϩ) (3,29); (ii) their spontaneous revertants (KPBj Rev) susceptible to the three antibiotic families (3); and (iii) mutants selected from these 3 revertant strains with cefoxitin, ciprofloxacin, or levofloxacin. For all experiments, K. pneumoniae strain ATCC 138821 was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Padilla et al also showed that a K. pneumoniae acrAB knockout mutant exhibited a lower capacity than the wild-type strain to cause pneumonia in a murine model (90). Bialek et al found that overexpression of the AcrAB efflux system in the Caenorhabditis elegans model is linked to an increased virulence potential in K. pneumoniae (91). Overall, these studies emphasize that the expression of efflux systems is a key factor in both antibiotic resistance and virulence in K. pneumoniae.…”
Section: Ribosomal Protection Tet44mentioning
confidence: 84%
“…The plates were incubated at 20 uC and scored daily for dead nematodes using a stereoscope (SMZ168 BN; Motic). Nematodes were agesynchronized with bleach and transferred every 2 days to fresh plates to eliminate overcrowding by progeny until they laid no further eggs (Bialek et al, 2010;Fuursted et al, 2012;Srinivasan et al, 2012). Worm mortality was scored over time for~20 days, with death defined when a worm no longer responded to touch.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the observed changes in the extracellular matrix triggered by overproduction of YfiN DGC and cellulose was next evaluated using a C. elegans infection model (Bialek et al, 2010;Fuursted et al, 2012;Srinivasan et al, 2012). Age-synchronized, adult nematodes were fed LM21gfp WT cells or isogenic mutants lacking yfiR, yfiN or yfiB, and mortality was scored over time, as an indirect marker of virulence potential.…”
Section: Cell Susceptibility and Survivalmentioning
confidence: 99%